Optimalisasi Pemasaran Digital Melalui Publikasi Website Pada UMKM - Hadiantini, Ratih; Sarifiyono, Aggi Panigoro (LPPM UNIBI, 2023)
The development of the internet is no longer limited to being a source of information or entertainment; it is now widely used for online transactions. This progress is supported by the hardware and software industries, which cater to the increasing public demand for internet-related services. These advancements have brought positive impacts to society, enabling the fast, accurate, and efficient access and processing of information. Additionally, other positive effects include advancements in the fields of economy, politics, society, technology, and other related sectors. Online transactions are highly beneficial as online businesses can reach all regions worldwide. This type of business, also known as e-commerce, is a modern business model offering various advantages compared to conventional businesses, which still have a strong appeal among the public. E-commerce has become an essential component for enterprises or companies to remain competitive in the global market